Non-native listeners perceiving foreign accentedness of English speech: new evidence from Chinese and Spanish listeners - Xue, Xiaojiao; Shan, Yixue; Wang, Xinyu; Dunham, Richard Erick (Círculo de Lingüística Aplicada a la Comunicación, 2023)
As an international language, English is an important tool for people of different native languages to communicate with each other. Many empirical studies, proving that foreign accents are prevalent in L2 learners’ oral English, involved native speakers as raters of foreign accents. This study compared the rating patterns of listeners from Chinese, Spanish and English language backgrounds with different English proficiencies for foreign accents in English speech and investigated the acoustical cues used by these listeners. Results showed that Chinese listeners, sharing language backgrounds with talkers, tended to be more tolerant for the Chinese accent in English speech. Spanish listeners had a stricter criterion for mild Chinese accents, proving that the influence of listeners’ L1 on their perception of foreign accents can be different for different degrees of accents. The effects of listeners’ L2 proficiency was found for Chinese listeners’ perception of accents and the number of acoustic predictors used by non-native English listeners. The study provides more evidence about the mechanism of native and non-native listeners’ perception of foreign accent and offers implications for the recruitment of raters for the assessment of oral English.